SEASONAL VARIATION, SUB–TYPE AND PRODROMAL ILLNESSES IN GUILLAIN–BARRE SYNDROME. Issue 11 (9th October 2013) - Brain, Susannah; Webb, Alastair; Zentar, Marc; Turner, Martin R
Abstract : Background: Studies have produced contradictory evidence for seasonal variation in the incidence of Guillain–Barre Syndrome (GBS), possibly due to the potentially confounding factor of the prodromal illness, for example peaks in Winter following influenza balanced by peaks in Summer due to diarrhoeal disease. The morbidity and mortality of GBS is influenced by the subtype of neuronal pathology, which may also depend upon the nature of the prodromal illness, for example axonal forms being associated with Campylobacter jejuni infection. In an attempt to study these interactions, we performed a retrospective cohort study of admission for GBS at a large teaching hospital to identify seasonal variation in incidence, subtype and associated prodromal illness. Methods: Patients admitted to the Oxford University Hospitals NHS Trust from 2001–2012 were initially identified as having a primary diagnosis of GBS by hospital coding. Seasons were defined as 3 month periods, starting from January to March (Winter). Clinical notes were then reviewed to confirm the diagnosis. Where available, the neurophysiological subtype and nature of any prodromal illness were identified. Variation in seasonal incidence was determined by chi–squared tests, and continuous variables were compared using ANOVA. Results: Over the 11 year period, 140 patients were confirmed as having GBS, comprising 111 AIDP, 10 AMAN, 6 ASMAN, 5 Miller Fisher, 8 undetermined. There was a significant variation in seasonal incidence (p=0.037), with GBS significantly more common in Winter versus Summer (48 versus 25, p=0.007), with comparable numbers in Autumn (33) and Spring (34). A shorter average length of stay was observed in Winter compared to other seasons (15 versus 25 days, p=0.02). A specific entry regarding prodromal illness was identifiable in the clinical notes of 59/140 (42%). Of these, 22 (37%) reported an influenza–like illness, and 19 (32%) a diarrhoeal illness. In these cases, the increased incidence of GBS in Winter was partly explained by an increased incidence of GBS preceded by an influenza–like illness in Winter versus Summer (14 versus 3, p=0.012). Although there was no significant relationship between prodromal illness and GBS subtype due to the low number of axonal forms, where identifiable, all cases of AMAN had a diarrhoeal prodromal illness. Conclusions: In this study population, we demonstrated a significant Winter peak of GBS admissions, which we interpret as being related to the increased incidence of influenza–like illnesses. Possible factors in the significantly shorter hospital stay we observed during these peak times include less severe cases, or the increased preparedness of acute services.